Extra-Intestinal Manifestations of Celiac Disease in Pediatric Population of a Tertiary Care Hospital in Rawalpindi, Pakistan - an Observational Study - Adnan,; Ullah, Hanif; Hasan, Shamama; Shamraiz, Ifnan; Khan , Husna (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency and types of extra-intestinal manifestations (EIMs) in children with celiac disease.Study Design: Observational study.Place and Duration of Study: Department of Pediatric Gastroenterology, Combined Military Hospital, Rawalpindi, Pakistan from Jan to Jun 2025.Methodology: The study included 233 children aged 1–15 years diagnosed with celiac disease based on ESPGHAN guidelines. Children with celiac crisis or other autoimmune/chronic illnesses were excluded. Data were collected through clinical examination and laboratory investigations. EIMs were identified using standard definitions. Statistical associations were analyzed using chi-square or Fisher’s exact test (p